Feasibility of the consortium of corn with buffel grass and tifton-9: a descriptive analysis (Research, Society and Development, 2022)
The is a system in which the same area, or more cultivars, are implanted, an objective of integration within crop-livestock that has as an alternative the consortium, consortium and/or alternative of agricultural and livestock activities of crop-livestock. property, in this sense, the present viable work objective, experienced the practical feasibility of the agroecological system, as experienced conditions and conditions of sustainable cultivation, in this sense, experienced in practical conditions of a sustainable cultivation system, in this sense, experienced, in conditions practices in an agroecological system. production center of the instituto federal do norte de minas in the city of Araçuaí, using brs 3046 corn, buffel grass and tifton 9. the corn was planted in a spacing of 90 cm between rows and 80cm between plants, fertilization was done the npk 04-14-08 applying 50g per square meter. tifton-9 grass was planted by broadcast, but no grass growth was observed, whereas buffel grass was planted by seedlings and height analysis was performed. Per plant, the height of the foot of the spike plant diseases In the end, it was found that there is practical feasibility of intercropping buffel grass and that it can be recommended to take advantage of the edaphoclimatic conditions of the Vale do Jequitinhonha.